2004
DOI: 10.1111/j.0001-5172.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased spillover of norepinephrine to the portal vein during CO2‐pneumoperitoneum in pigs

Abstract: Estimated norepinephrine spillover from the drainage area of the portal vein increased during CO2-pneumoperitoneum in pigs. This may indicate that the increased norepinephrine concentrations found in arterial plasma reflects a local activation of sympathetic nerves in the region of the portal drainage area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Although the mechanism underlying this phenomenon is largely unknown, direct compression of the renal parenchyma and renal vein, and the release of vasoconstrictors, such as vasopressin, angiotensin II, and catecholamines, have been well documented to reduce intraoperative urine output [10,11]. Even though oliguria is known to be transient and to resolve after desufflation in men [2-4], the use of vasodilators such as nitroglycerine [1], diltiazem [12], and nicardipine [6], and low doses of dopamine [13] has been suggested to prevent renal dysfunction during pneumoperitoneum without causing any hemodynamic derangement.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying this phenomenon is largely unknown, direct compression of the renal parenchyma and renal vein, and the release of vasoconstrictors, such as vasopressin, angiotensin II, and catecholamines, have been well documented to reduce intraoperative urine output [10,11]. Even though oliguria is known to be transient and to resolve after desufflation in men [2-4], the use of vasodilators such as nitroglycerine [1], diltiazem [12], and nicardipine [6], and low doses of dopamine [13] has been suggested to prevent renal dysfunction during pneumoperitoneum without causing any hemodynamic derangement.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma norepinephrine is almost entirely derived from sympathetic nerve terminals and plasma epinephrine is derived from the adrenal medulla. Myre et al [2,17] determined catecholamine levels in the radial artery and superior vena cava in animals after induction of PN. They found an increase in norepinephrine levels, whereas epinephrine levels remained unchanged and suggested that the increase in plasma norepinephrine may be due to more local activation of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, specific patient positions during certain laparoscopic operations may further affect important hemodynamic parameters. Several literature reports based on laboratory and clinical parameters have given controversial results concerning hemodynamic changes as well as endocrine responses during PN [1,2,3]. Treatments with clonidine, β-blockers, sodium nitroprusside and intravenous administration of fluid were tested to eliminate negative hemodynamic effects of PN in various animal studies [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for portal vein access in swine for pharmacological studies, for investigations of the nutrition physiology and many other physiological and pathophysiological studies [6][7][8][9][10][11] . Focused on pharmacology, a wide spectrum of drug combinations can be investigated for their metabolic pathways and related pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%